Faktor yang Berhubungan dengan Kejadian Gizi Lebih dan Obesitas pada Remaja - Masyitoh, Masyitoh; Budiono, Irwan (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: The prevalence of overweight and obesity in adolescents in Kelurahan Pela Mampang, Kecamatan Mampang Prapatan, South Jakarta has increased 31,1%. due to the COVID-19 pandemic. This study aims to analyze the factors that associated with the incidence of overweight and obesity in adolescents. Methods: This research is an observational analytic study conducted in a cross sectional design. The sample used in this study were 62 adolescents in Kelurahan Pela Mampang, Kecamatan Mampang Prapatan, South Jakarta, which were selected by using random sampling technique. Results: The analysis used univariate and bivariate analysis with Chi Square test and alternative test using fisher's test. The result of bivariate analysis showed a relevance between the incidence of overweight and obesity with energy intake, physical activity, frequency consumption of junk food, sleep quality, and frequency of ordering food with online applications (p-value<0,05). While from other variables such as family income the education level of mothers, history of parents with overweight and obesity, time screen, and home quarantine has no connection between the incidence of overweight and obesity (p-value>0,05). Conclusions: Based on this research, it was recommended for adolescents to care about their nutritional status and concern to factors that can affect the incidence of overweight and obesity.